Study of Political Branding through TikTok Accounts of Indonesian Presidential Candidates - Frasetya, Vito; Wibawa, Agung (KOMUNIKA, 2023)
Early in 2024, there will be a simultaneous general election in Indonesia. The presidential election is receiving interest from the general populace. Social media is being used by the presidential contenders for 2024–2029 to promote their campaigns. We are Social claims that TikTok is the most widely used social media platform in Indonesia. As social media platforms continue to play a crucial role in modern political campaigns, TikTok has emerged as a significant tool for candidates to engage with the electorate, particularly the younger demographic. These candidates engaged in political branding. This research uses a qualitative approach using image analysis from Christopher Pich, by collecting data from TikTok with exolyt analysis tools in the form of narratives and video uploads of presidential candidates. The content on each candidate's official TikTok account was examined as part of the analysis. The findings indicate that Prabowo Subianto was not visible on his official TikTok social media account, while Anies Baswedan created a story about change and projected a religious image on his account. Meanwhile, Ganjar created stories about how to sustain development, identified himself with white hair, and was a servant of the people.